Renda básica universal: uma análise da necessidade, justiça e viabilidade jurídica no Brasil - Bronfmann, José Leopoldo Tiecher (Universidade do Vale do Rio dos Sinos, 2023)
This research has as its theme the legal viability of implementing in Brazil an income distribution program without conditionalities. In the context of the Fourth Industrial Revolution society, changes are increasingly being seen in the way labor is being provided, either with the migration of jobs to other forms of work, or with the supplantation of the human being through automation and digitalization of processes. The general objective was to investigate whether, and in what way, an income distribution program without conditionalities can be legally adequate to succeed the search for full employment in Brazil. The specific objectives were listed below: a) describe the history of social assistance, identifying the different stages of its evolution in the world and in Brazil, identifying the functioning and organization of the Unified Social Assistance System; b) analyze the current context of labor and its perspectives in the light of the Fourth Industrial Revolution; c) verify how poverty affronts human dignity; d) inquire about the different conceptions of social justice, verifying whether a universal basic income program would be in accordance with these perspectives; e) analyze Universal Basic Income as an alternative to full employment; f) analyze the structuring and non-structuring elements of universal basic income; g) verify the legal adequacy of the universal basic income, recommending guidelines for the implementation of a program with these characteristics in Brazil. Thus, the first chapter intended to describe the history of social assistance. Under the second chapter, four distinct factors are covered which, when jointly analyzed, give foundation, within the scope of this research, to the institution of a universal basic income: 1) The Fourth Industrial Revolution and technological unemployment threaten both traditional jobs and new forms of human work; 2) poverty, which can be the result of new productive arrangements, is not consistent with human dignity, which needs to be preserved; 3) if the method found is the institution of an unconditional income distribution program, it must be verified that the social dividend to be delivered is socially fair; 4) finally, the basic income strategy was compared with the traditional full employment policy. The hypothetical-deductive method was adopted, in order to achieve the pretensions of these first two chapters, through a bibliographic review. Through deductive logic, it was intended to obtain partial conclusions about the themes addressed in each of the chapters. In the third chapter, the structuring elements of a basic income program were identified, finding different dimensions, which were classified as sensitive and non-sensitive, in order to propose the best positioning in each one of them. To this end, along with a bibliographical and jurisprudential review, the inductive method was adopted, in order to end the research with a delivery to Brazilian society. Based on the analysis of precedents, the best legal form was inferred for the implementation of basic income in Brazil.
Keywords: Renda Básica Universal; Quarta Revolução Industrial; Desemprego tecnológico; Dignidade humana; Justiça social; Universal Basic Income; Fourth Industrial Revolution; Technological unemployment; Human dignity; Social justice; ACCNPQ::Ciências Sociais Aplicadas::Direito